A Knowledge-Based Service Composition Algorithm with Better QoS in Semantic Overlay. (30th March 2015) - Dai, Huijun; Qu, Hua; Zhao, Jihong
Abstract : A semantic overlay network (SON) is a visual framework clustered under similar metaknowledge units such as ontologies, algorithms, and rule engines. Knowledge-based service composition (KC) has become a prominent aspect of building new and creative composed service through a combination of semantically similar information at the knowledge level. In this study, a promising approach to construct a standard knowledge model is developed to utilize the progress of KC. To evaluate and optimize the composition, we define the quantity of service (QoS) regarding user requirements in the KC instance, and a KC instance path with better QoS is found in the model using the KC algorithm. Simulation results prove that our approach has a tradeoff between efficiency and equality.